Annual Plan 1978-79 Hill Region Uttar Pradesh - Planning Commission (Planning Commission, 1978)
The hill region of the state lies in the north along the himalayas and comprises eight districts of Nainital, Ahmira, Pithoragarh, Dehra- Dun, Uttarkashi, kauri Garhwal, Tehri Garhwal and Chamoli. The entire region is mountainous except a few plains between the ridges and plain and tarai areas of Dehradun and Nainital Districts. The Hill areas on account of their topography, peculiar geophysical features and special problems form a distinct socio-economic region as compared to the plains.
Hill Development Department, Uttar Pradesh